How to take the grrrr out of anger - Verdick, Elizabeth (Laugh & learn., 2015)
"Kids need help learning how to manage their anger. Blending solid information and sound advice with humor and lively illustrations, these anger-management tips guide kids to understand that anger is normal and to learn they can express it in healthy ways. The book teaches them how to recognize anger in themselves and others, how to handle situations and emotions (loneliness, guilt, frustration, fear) that lead to or mask anger, and how to deal with the anger they feel. This revised edition addresses children's exposure to increased societal violence and includes discussion and examples of anger related to texting and social media. Young readers learn that cruelty and violence are not acceptable and there are safer, more positive ways to resolve conflicts. They also discover what to do when people around them are angry, how to get help, and how to locate other resources when they need more support"--